Effect of marital distance on birth weight and length of offspring - Kozieł, Sławomir; Danel, Dariusz P.; Dziedzic-Danel, Antonina; Zaręba, Monika (Anthropological Review, 2017)
Marital distance (MD), the geographical distance between birthplaces of spouses, is considered an agent favouring occurrence of heterosis and can be used as a measure of its level. Heterosis itself is a phenomenon of hybrid vigour and seems to be an important factor regulating human growth and development. The main aim of the study is to examine potential effects of MD on birth weight and length of offspring, controlling for socioeconomic status (SES), mother’s age and birth order. Birth weight (2562 boys and 2572 girls) and length (2526 boys, 2542 girls) of children born in Ostrowiec Swietokrzyski (Poland) in 1980, 1983, 1985 and 1988 were recorded during cross-sectional surveys carried out between 1994-1999. Data regarding the socio-demographic variables of families were provided by the parents. Analysis of covariance showed that MD significantly affected both birth weight and length, allowing for sex, birth order, mother’s age and SES of family. For both sexes, a greater marital distance was associated with a higher birth weight and a longer birth length. Our results support the hypothesis that a greater geographical distance between the birth places of parents may contribute to the heterosis effects in offspring. Better birth outcomes may be one of the manifestations of these effects.